Transgenic Expression of a Mutant Ribonuclease Regnase-1 in T Cells Disturbs T Cell Development and Functions - Kong, Gangcheng; Dou, Yaling; Xiao, Xiang; Wang, Yixuan; Ming, Yingzi; Li, Xian C. (Frontiers in Immunology, 2021)
Regnase-1 is an RNA-binding protein with ribonuclease activities, and once induced it controls diverse immune responses by degrading mRNAs that encode inflammatory cytokines and costimulatory molecules, thus exerting potent anti-inflammatory functions. However, Regnase-1 is extremely sensitive to degradation by proteases and therefore short-lived. Here, we constructed a mutant Regnase-1 that is resistant to degradation and expressed this mutant in vivo as a transgene specifically in T cells. We found that the mutant Regnase-1 transgenic mice exhibited profound lymphopenia in the periphery despite grossly normal spleen and lymph nodes, and spontaneously accepted skin allografts without any treatment. Mechanistic studies showed that in the transgenic mice thymic T cell development was disrupted, such that most of the developing thymocytes were arrested at the double positive stage, with few mature CD4+ and CD8+ T cells in the thymus and periphery. Our findings suggest that interfering with the dynamic Regnase-1 expression in T cells disrupts T cell development and functions and further studies are warranted to uncover the mechanisms involved.